Pengaruh ROA, BOPO Dan FDR Terhadap Tingkat Bagi Hasil Deposito Mudhrabah - Neneng Uswatun Hasanah; Wirman Munaraja (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2022)
This study aims to understand and determine the effect of ROA, BOPO and FDR on the rate of profit sharing fordeposits mudharabah conducted at PT Bank BRI Syariah in 2012-2020. The research was assisted by the SPSS 16 program. The type of secondary data with quantitative data was in the form of quarterly financial report data. The population in this study is the financial statements of PT Bank BRI Syariah registered with the OJK, the reports selected as samples are quarterly reports in 2012-2020. The technique used is purposive sampling. Based on the results of the hypothesis, it shows that the ROA, BOPO and FDR variables have no partial effect on the variable rate of profit sharing fordeposits mudharabah, then simultaneously there is no effect between the ROA, BOPO and FDR variables on the variable rate of profit sharing fordeposits mudharabah, with a Rsquar value of 40%. , while the rest can be influenced by other variables or factors not included in this study.